Joy ride - Abrams, J. J. 1966- (Jeffrey Jacob); Moore, Chris; Tarver, Clay; Dahl, John, 1956-; Zahn, Steve, 1968-; Walker, Paul, 1973-; Sobieski, Leelee, 1983-; Bowman, Jessica, 1980-; Beltrami, Marco; Jur, Jeffrey; Regency Enterprises; New Regency (Firm); et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2002)
It's all fun and games when two brothers take off cross-country to bring home a pretty college friend. But the jokes end when a prank backfires and they find themselves stalked by a vengeful trucker who won't give up his relentless chase until somebody pays with their life.
Screen format: anamorphic widescreen (aspect ratio 2.35:1).
Originally produced as a motion picture in 2001.
Special features: commentary by director John Dahl, commentary by J.J. Abrams and Clay Tarver, commentary by Steve Zahn and Leelee Sobieski, deleted scene and alternate endings, theatrical trailer, featurette, "More than one rusty nail", "More than one joy ride."
Music by Marco Beltrami ; edited by Eric L. Beason, Glen Scantlebury ; production designed by Rob Pearson ; director of photography, Jeffrey Jur ; executive producers, Arnon Milchan, Patrick Markey, Bridget Johnson.
Steve Zahn, Paul Walker, Leelee Sobieski, Jessica Bowman.
MPAA rating: R.
Keywords: College students -- Drama; Truck drivers -- Drama; Practical jokes -- Drama; Road films; Fiction films; Video recordings for the hearing impaired; Thriller films; Feature films